2021
DOI: 10.1371/journal.pone.0247201
|View full text |Cite
|
Sign up to set email alerts
|

Reducing underreporting of abortion in surveys: Results from two test applications of the list experiment method in Malawi and Senegal

Abstract: Background Accurately measuring abortion incidence poses many challenges. The list experiment is a method designed to increase the reporting of sensitive or stigmatized behaviors in surveys, but has only recently been applied to the measurement of abortion. To further test the utility of the list experiment for measuring abortion incidence, we conducted list experiments in two countries, over two time periods. Materials and methods The list experiment is an indirect method of measuring sensitive experiences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Recalling past experiences using a two-year time marker may not be salient in this population. Another study using UTHA cohort data suggested that recalling the timing of specific events may be inaccurate in this lownumeracy population [37]. It is possible that women reported trying for two years to become pregnant, but, in fact, they had tried for a shorter amount of time.…”
Section: Plos Global Public Healthmentioning
confidence: 98%
“…Recalling past experiences using a two-year time marker may not be salient in this population. Another study using UTHA cohort data suggested that recalling the timing of specific events may be inaccurate in this lownumeracy population [37]. It is possible that women reported trying for two years to become pregnant, but, in fact, they had tried for a shorter amount of time.…”
Section: Plos Global Public Healthmentioning
confidence: 98%
“…In the second wave of this survey, direct questioning yielded a prevalence of 97% and 78% via the list experiment (Treibich & Lépine, 2019 ), implying the use of condoms is a socially desirable behavior and is over‐reported. Previously, the list experiment method has been used for eliciting self‐reported answers for topics including abortion (Bell & Bishai, 2019 ; Moseson et al., 2021 ), voting preferences (Gonzalez‐Ocantos et al., 2012 ; Holbrook & Krosnick, 2010 ), use of micro‐finance loans (Karlan & Zinman, 2012 ), opinions on undocumented migrants (McKenzie & Siegel, 2013 ), gay marriage (Lax et al., 2016 ) and racism (Krumpal, 2013 ) and has been shown to be effective to measure condom use (LaBrie & Earleywine, 2000 ).…”
Section: Data and Descriptive Analysismentioning
confidence: 99%
“…The indirect nature of measures like the list experiment are expected to yield a higher estimate of abortion utilization compared to direct questions, because there is greater privacy afforded to the respondent and their experiences are less visible to the researcher. Indeed, list experiment estimates of abortion have improved reporting over direct measures in several studies of abortion utilization in Iran, Liberia, Pakistan, Senegal, and the US [ 13 17 , 22 , 23 ]. However, the list experiment has not always succeeded in reducing underreporting.…”
Section: Introductionmentioning
confidence: 99%
“…However, the list experiment has not always succeeded in reducing underreporting. Several applications of the list experiment to measure abortion have failed to find higher estimates than direct questions, such as in studies conducted in Malawi, Turkey, Tanzania, and Vietnam [ 18 22 ]. Given the mixed performance of list experiments in measuring abortion across contexts, the method requires further study.…”
Section: Introductionmentioning
confidence: 99%